Important Compression and Export Performance in Developing Countries - Khan, Mohsin S.; Knight, Malcolm D. (The Review of Economics and Statistics, 1988)
The debt crisis that began in 1982 forced a number of developing countries that had relied on external financing into rapid adjustment of their current account positions. In many of these countries external adjustment mainly took the form of import reduction, or what has been termed 'import compression,' to generate trade balance surpluses necessary to service the existing stock of foreign debt. While the effects of import compression on consumption and growth have been discussed in the literature, there has been little concern expressed with regard to the direct effects such a policy can have on export performance. This paper develops a model that takes explicit account of the feedbacks between imports and exports that arise through the effects of imported inputs on exports and the availability of foreign exchange on imports. Empirical tests of this model for 34 developing countries tend to confirm both these hypotheses. These results point clearly for additional foreign financing to reduce the need for import compression and its attendant-negative effects on the supply of exports.